EVALUASI ERGONOMI PADA PENGOPERASIAN MESIN EKSTRUDER DI PT. XYZ UNTUK MENGURANGI RISIKO MUSCULOSKELETAL DISORDERS - Hernata, Ananda Abdillah (Jurnal Inovisi (Teknik Industri), 2025)
The operation of extruder machines in the cable industry shows the highest contribution to musculoskeletal disorders (MSDs) at PT. XYZ. Of the 93 cases in January–June 2025, 41 cases occurred in the extruder area. This study focused on an ergonomic evaluation of the IS-10 machine (shift 1) during April–July 2025 to map risks and formulate practical interventions. The methods used included REBA (Rapid Entire Body Assessment), NBM (Nordic Body Map), and RWL (Recommended Weight Limit). Data were collected through observation, posture documentation, short interviews, and NBM questionnaires. The results showed that most activities were at a moderate to high risk level, with the peak risk in the material lifting process (process 7) and the highest final REBA score reaching 10 in the second worker. MSD complaints based on the NBM of the second worker were the highest. The RWL assessment showed a Lifting Index (LI) of 3.1—exceeding the safe threshold—which indicates that manual material handling work has a significant risk of injury. Recommendations: (1) preparation of ergonomic SOPs, (2) procurement of lifting aids, and (3) work posture training. These interventions are expected to reduce the risk of MSDs and increase comfort and work productivity.